2016
DOI: 10.1146/annurev-fluid-010814-013619
|View full text |Cite
|
Sign up to set email alerts
|

Contrail Modeling and Simulation

Abstract: There is large uncertainty in the radiative forcing induced by aircraft contrails, particularly after they transform to cirrus. It has recently become possible to simulate contrail evolution for long periods after their formation. We review the main physical processes and simulation efforts in the four phases of contrail evolution, namely the jet, vortex, vortex dissipation, and diffusion phases. Recommendations for further work are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 163 publications
2
64
0
1
Order By: Relevance
“…The underlying conceptual framework‐sketched Figure is borne out by airborne observations [ Voigt et al , ] and LES [ Paoli and Shariff , ]. The ice crystal sublimation efficiency, ξ , defines the ratio between contrail ice crystal number concentrations (per unit volume of air) before (plume age t v ) and after ( t v +Δ t v ) wake vortex processing ξ=n(tv+Δtv)n(tv)=false(1η)fpwprimary wake (pw)0.3em0.3em+falseηscriptDswsecondary wake (sw)0.3em. While n ( t v ) decreases by isobaric mixing by a factor scriptDsw in the fraction of detrained exhaust, it is affected by sublimation losses in the exhaust trapped in the sinking (heating) vortices in which mixing is strongly suppressed.…”
Section: Wake Processing Of Ice Crystals In Persistent Contrailsmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying conceptual framework‐sketched Figure is borne out by airborne observations [ Voigt et al , ] and LES [ Paoli and Shariff , ]. The ice crystal sublimation efficiency, ξ , defines the ratio between contrail ice crystal number concentrations (per unit volume of air) before (plume age t v ) and after ( t v +Δ t v ) wake vortex processing ξ=n(tv+Δtv)n(tv)=false(1η)fpwprimary wake (pw)0.3em0.3em+falseηscriptDswsecondary wake (sw)0.3em. While n ( t v ) decreases by isobaric mixing by a factor scriptDsw in the fraction of detrained exhaust, it is affected by sublimation losses in the exhaust trapped in the sinking (heating) vortices in which mixing is strongly suppressed.…”
Section: Wake Processing Of Ice Crystals In Persistent Contrailsmentioning
confidence: 99%
“…The underlying conceptual framework-sketched Figure 1 is borne out by airborne observations [Voigt et al, 2010] and LES [Paoli and Shariff , 2016]. The ice crystal sublimation efficiency, , defines the ratio between contrail ice crystal number concentrations (per unit volume of air) before (plume age t v ) and after (t v + Δt v ) wake vortex processing…”
Section: Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluid-dynamical models (Huebsch & Lewellen, 2006;Unterstrasser, 2016) and measurements Schumann et al, 2013) have shown that aircraft wake dynamics can have marked effects on contrail properties. This includes the possibility of ice particle losses during the descent of wake vortices Geophysical Research Letters 10.1029/2018GL079390 forcing ice particle sublimation due to adiabatic heating even if the ambient air surrounding the contrail is ice-supersaturated (Kärcher, 2018;Paoli & Shariff, 2016). Assessing contrail properties toward the end of the vortex phase is of particular interest, as they affect properties of evolving contrail cirrus over hours (Unterstrasser & Gierens, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Modeling tools with various degrees of complexity have been developed to study formation stage processes, ranging from microphysical parcel models to fluid‐dynamical large‐eddy simulations (LES; see Paoli & Shariff, , and references therein). Detailed model validation is hampered primarily by a lack of contrail measurements in ice‐supersaturated conditions.…”
Section: Introductionmentioning
confidence: 99%